2022
DOI: 10.1038/s41598-022-07975-x
|View full text |Cite
|
Sign up to set email alerts
|

Inter-limb asymmetry of kinetic and electromyographic during walking in patients with chronic ankle instability

Abstract: After an initial ankle sprain, a relevant number of participants develop chronic ankle instability (CAI). Compensatory strategies in patients with CAI may change the inter-limb symmetry needed for absorbing movement-related forces. Accordingly, an increased risk of injury can occur. The present study aimed to compare the inter-limb asymmetry of kinetic and electromyography between individuals with CAI and without a history of an ankle sprain (Non-CAI) during walking. In this cross-sectional study, fifty-six at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…In this study, the injured side showed higher LR after MF, consistent with Tajdini et al (2022) that patients with ankle instability exhibited a greater inter-limb asymmetry of LR, and the LR of their injured side was higher than healthy individuals during walking. As we found in kinematics, the FAI population after MF cannot effectively control the ankle inversion angle.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the injured side showed higher LR after MF, consistent with Tajdini et al (2022) that patients with ankle instability exhibited a greater inter-limb asymmetry of LR, and the LR of their injured side was higher than healthy individuals during walking. As we found in kinematics, the FAI population after MF cannot effectively control the ankle inversion angle.…”
Section: Discussionsupporting
confidence: 89%
“…12,13 It may reduce the ability to absorb impact and modulate vertical ground reaction force appropriately during heel strike. 14 In addition, patients with CAI demonstrated different muscle activation pattern of lower extremity during gait in the tibialis anterior and peroneus longus. 13,15,16 Changes in the activation patterns of tibi-alis anterior and peroneus longus could induce a more supinated foot position during the stance phase, 15 which could result in repeated ankle instability, recurrent sprains, a feeling of the "giving away," and pain.…”
Section: Introductionmentioning
confidence: 96%
“…Chronic Ankle Instability (CAI) emerges as a common consequence of Lateral Ankle Sprain (LAS), manifesting as functional decline and reported instability. This condition significantly predisposes individuals to recurrent ankle sprains and eventually osteoarthritis, leading to substantial medical expenses and presenting a noteworthy public health concern [1] Following an initial ankle sprain, 40% of patients experience persistent symptoms, including recurrent sprains, subjective instability, and disabling issues such as pain and swelling even a year post-injury [2] The International Ankle Consort [3] identifies both LAS and CAI as significant global healthcare issues, emphasizing the long-term physical and functional impairments affecting health-related quality of life and extending to proximal body regions due to compensations in the sensorimotor and biomechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…CAI not only damages the sensorimotor system but also alters the dynamic restraint mechanisms in the lower extremity, resulting in impaired joint loading and reduced joint protection against impairments [2] These constraints on the sensorimotor systems create a continuum of impairments [4] [5] As a consequence of the initial injury, the impairment in the sensorimotor system has the potential to induce neuromuscular changes. These changes can manifest in faulty movement patterns [6] such as alterations in Dynamic knee valgus (DKV) and subsequent dynamic Q angle during various functional tasks.…”
Section: Introductionmentioning
confidence: 99%